Effect of Ralgro and Compudose on grazing steer performance - Lyle W. Lomas (Kansas Agricultural Experiment Station Research Reports, 1982)
COMPUDOSE (an estradiol removable implant) increased steer gains during 202 days of grazing by 11.4%. Ralgro implants (once at the beginning of the study) increased gain 8.5%. Steer performance on the two implants was statistically similar.
Keywords: Cattlemen& #x27; s Day; 1982; Report of progress (Kansas State University. Agricultural Experiment Station); 413; Beef; Ralgro; Compudose; Steer performance